FOSTERING CROSS-CULTURAL COMPETENCE: THE ROLE OF ENGLISH EDUCATION IN MANAGEMENT AND ITS IMPACT ON PREPAREDNESS FOR GLOBAL INTERACTIONS - Fitayanti, Sri (Universitas PGRI Sumatera Barat, 2023)
This study investigates the pivotal role of cultural sensitivity and enhanced communication skills, developed through English education, in preparing management students for successful cross-cultural interactions. Thirty students, faculty members, and industry professionals participated in this qualitative research. Students were enrolled at STIE Port Numbay Jayapura. Data were collected through in-depth interviews and focus group discussions, followed by thematic content analysis. Management students reported elevated cultural awareness and enhanced English communication skills. They felt well-prepared for cross-cultural interactions, emphasizing the role of English proficiency. Faculty members recognized the need for curriculum enhancement and tailoring instruction to nurture English competence. Industry professionals acknowledged graduates' English competence but stressed the importance of practical application. Cultural sensitivity and English language proficiency are crucial for management students in a globalized world. Curriculum enhancement and practical application are essential. Future research can explore these themes in diverse contexts.